A PLA alloy, a foamed sheet and a preparation method thereof

By introducing ionic liquid into the PLA alloy and forming a crosslinked structure, the problem of easy threading and bursting of PLA foaming materials during the foaming process is solved, and a high foaming ratio and high strength PLA foamed sheet is achieved, and environmentally friendly supercritical CO2 is used as the foaming agent.

CN116462945BActive Publication Date: 2025-04-01WANHUA CHEMICAL (NINGBO) CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202310361669.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-07
Publication Date
2025-04-01
Estimated Expiration
2043-04-07

AI Technical Summary

Technical Problem

The existing PLA foaming materials are prone to threading holes and bursting during the foaming process, forming a large number of open-cell structures, which limits their application in the foaming field. Moreover, traditional foaming agents such as Freon are not conducive to environmental protection.

Method used

Using a PLA alloy containing ionic liquid, the PLA carries epoxy groups by reacting excessive chain extender with PLA resin, and then ionic liquid is added to the middle section of the extruder to form a crosslinked structure, and the ionic liquid is used to absorb and capture CO2 to improve the foaming ratio.

Benefits of technology

Foamed sheets with high foaming ratio (23-27 times), high compression strength (0.11-0.14MPa) and high compression modulus (3.5-3.8MPa) were achieved, and environmentally friendly supercritical CO2 was used as the foaming agent.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention discloses a PLA alloy, a foam sheet and a preparation method thereof. The PLA alloy comprises the following components: PLA resin, talcum powder, anti-hydrolysis agent, chain extender, antioxidant, plasticizer, and ionic liquid. The present invention cleverly designs the order of adding materials, and according to the acid value of the PLA resin, designs to add an excessive amount of chain extender to react with the PLA resin first, so that the PLA has an epoxy group, and then adds an ionic liquid in the middle section of the extruder. The ionic liquid is a green solvent with excellent properties such as extremely low volatility, non-flammability, designability, and acidic gas affinity. It can absorb and capture acidic gases such as CO2 and CO, and can react with the epoxy groups on the PLA at the same time, grafted onto the PLA molecule and form a cross-linked structure. In the process of foaming, CO2 is not easy to escape, and the foaming ratio is improved. The foaming ratio of the foam sheet prepared by this method can reach 23-27 times, the compression strength is 0.11-0.14Mpa, and the compression modulus is 3.5-3.8Mpa.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of degradable plastics, and in particular relates to a PLA alloy, a PLA alloy with good compatibility with CO2, a foaming material and a preparation method thereof. Background Art

[0002] As people's awareness of ecological and environmental protection increases, countries have successively introduced "plastic restriction and plastic ban" policies and regulations. Biodegradable plastics have received more and more attention, and their application areas are constantly expanding.

[0003] At present, the cushioning packaging in the express delivery industry and the foam lunch boxes in the take-out industry are used in large quantities and are all made of non-degradable foam materials, which are difficult to recycle and have a certain impact on the environment. In the future, the development of degradable foam materials will attract more and more attention.

[0004] Polylactic acid (PLA) is a biodegradable material with excellent performance. Its degradation rate is greater than 90% after 180 days in a composting environment. It has high strength and good processability and can be used to prepare rigid foaming materials. However, its linear structure and low melt strength limit its foaming ratio. It is easy to form holes and bubbles during the foaming process, forming a large number of open-pore structures, which limits its application in the foaming field.

[0005] CN109762313A discloses a method for preparing a high-ratio polylactic acid foamed sheet. The alloy is composed of polylactic acid, a nucleating agent, a foaming agent, and other additives. After primary extrusion, secondary extrusion, and extrusion foaming sheet, the sheet foaming ratio is 13 to 16 times, the pore diameter is uniform, the sheet thickness is uniform, the material has no perforation or bubble breaking, and the sheet pore structure is stable. However, the invention uses a fluorine-containing foaming agent, which is not conducive to environmental protection and does not conform to the concept of sustainable development.

[0006] CN109776848A discloses a method and device for directly preparing polylactic acid foamed products from polylactic acid polymer melt, the method comprising: polylactic acid melt preparation, feeding and secondary extrusion treatment; the method does not require water-cooled pelletizing, repeated drying and cooling, heating and melting and mixing, etc., thus avoiding the influence on the foaming performance, ensuring both the foaming performance and the quality, saving more than 1 / 3 of the energy consumption, and the obtained product foaming ratio is adjustable from 3 to 25 times, but the equipment used in the method occupies a large area, the polymerization process is not easy to control, and it is difficult to industrialize.

[0007] CN112940468A discloses a polylactic acid-based foamed particle and a preparation method thereof, wherein the prepared PLA foamed beads have a high expansion ratio and a uniform distribution of pore sizes. However, the preparation process of the foamed product is relatively complicated, and the particles are first saturated, then foamed to obtain primary foamed particles, then saturated again, then foamed for a second time, and finally steam-thermoformed to obtain the foamed product, which is not conducive to industrialization, and the foaming ratio of the foaming by the autoclave equipment is not easy to control, and it is difficult to meet the requirements of customers for foaming materials with a stable ratio.

[0008] CN108586963A discloses an application of an ionic liquid block polymer in supercritical carbon dioxide microporous foaming. The ionic liquid block polymer is synthesized by the RAFT method, which can play a heterogeneous nucleation role in the polymer foaming process, achieving the dual effects of heterogeneous nucleation and CO2 adsorption rate improvement, thereby realizing polymer supercritical CO2 microporous foaming. However, its synthesis process is relatively cumbersome, and after adsorbing CO2, it is difficult to lock CO2 due to the lack of cross-linking or branching structure, which may cause low foaming ratio, collapse after foaming, etc.

[0009] CN112426865A discloses a method for capturing CO2 in a composition, releasing the CO2 from the composition, and subsequent regeneration of the composition for reuse, which can be used to capture CO2 from waste streams from power plants, cement manufacturing, steel manufacturing, glass manufacturing, brewing, synthesis gas production, natural gas and biogas purification, ammonia synthesis or any other industrial process that produces acidic gases, but does not mention its application in CO2 foaming.

[0010] CN103910820A discloses a hexahedral silsesquioxane-based hyperbranched polymer and its application in supercritical carbon dioxide foaming. Ionic liquid is used as a monomer for synthesizing POSS-based hyperbranched polymers, and its role in capturing CO2 is not mentioned. The synthesized POSS-based hyperbranched polymer is used as a nucleating agent in polymer supercritical CO2 foaming to prepare a polymer foaming material.

[0011] Traditional physical foaming agents, such as Freon and butane, are not environmentally friendly, so supercritical CO2 and other environmentally friendly foaming agents have received widespread attention. Due to the inertness and low viscosity of CO2, it is incompatible with polymers and difficult to mix, forming a heterogeneous system, which makes it have a lower solubility and high diffusion coefficient in the polymer matrix. Therefore, it is difficult to use it as a foaming agent to prepare foamed products with high foaming ratio and uniform and stable pores. Summary of the invention

[0012] The present invention provides a PLA alloy having good compatibility with a foaming agent, a foaming material and a preparation method thereof. The PLA alloy contains an ionic liquid. An excess chain extender is first reacted with a PLA resin to allow the PLA to carry an epoxy group, and then the ionic liquid is added to the middle section of the extruder. The ionic liquid is a green solvent with excellent properties such as extremely low volatility, non-flammability, designability, and acidic gas affinity. It can absorb and capture acidic gases such as CO2, and can react with the epoxy groups on the PLA, be grafted onto the PLA molecules and form a cross-linked structure. During the foaming process, CO2 is not easy to escape, and the foaming ratio is increased. The foaming ratio of the foamed sheet prepared by this method can reach 23-27 times, the compression strength is 0.11-0.14Mpa, and the compression modulus is 3.5-3.8Mpa.

[0013] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0014] A PLA alloy comprising the following components:

[0015]

[0016] The melt index of the PLA resin of the present invention is 2-8 g / 10 min (190° C., 2.16 kg), preferably 4-7 g / 10 min (190° C., 2.16 kg). Suitable examples include but are not limited to LX575, LX175, LX530 from Total Corbion, 4032D, 8052D, 2002D from Natureworks, REVODE110, REVODE190, REVODE101 from Zhejiang Hisun, FY801, FY802, FY804 from Anhui Fengyuan, and one or more of LX575 and LX175 from Total Corbion; preferably one or more of FY801, FY802, FY804 from Anhui Fengyuan.

[0017] The anti-hydrolysis agent of the present invention is one or more of monomeric carbodiimide and polymeric carbodiimide. Suitable examples include but are not limited to STABAXOL 1LF of Rhein Chemie, HyMax 210 and HyMax 1010 of Langyi Chemical.

[0018] The chain extender of the present invention is one or more polyepoxides, and suitable examples include but are not limited to ADR4468, ADR4370, and ADR4400 of BASF.

[0019] The antioxidant of the present invention is one or more of amine antioxidants, hindered phenol antioxidants, thioester antioxidants, and phosphite antioxidants. Suitable examples include but are not limited to Sunshow's antioxidant 1010 and antioxidant 168.

[0020] The plasticizer described in the present invention is one or more of tributyl citrate, epoxy soybean oil, monoglyceride and dibutyl adipate.

[0021] The ionic liquid described in the present invention is one or more of tetramethylethylenediamine sulfonate onium salt, trioctylmethylamine bistrifluoromethanesulfonimide salt (375395-33-8), and 3-[(3-acrylamidopropyl)dimethylammonium]propionate (79704-35-1).

[0022]

[0023] The preparation method of the PLA alloy of the present invention comprises the following steps: mixing PLA resin, talcum powder, anti-hydrolysis agent, chain extender, antioxidant and plasticizer, adding the mixture to the main feeding port of a twin-screw extruder, adding an ionic liquid to the middle section of the extruder, then melting and extruding, cooling, pelletizing and drying.

[0024] In the preparation method of the PLA alloy of the present invention, the rotation speed of the twin-screw extruder is 200-600 rpm, and the extrusion temperature is 160-200°C.

[0025] A foaming material comprises the PLA alloy described in the present invention.

[0026] A method for preparing a foamed sheet comprises the following steps: extruding a foamed sheet from a PLA alloy on a foaming extruder.

[0027] The foaming extruder of the present invention adopts a 35 / 65 machine series single screw extrusion system, the temperature range of the primary screw extruder is controlled between 180 and 250° C., and the rotation speed is 20-50 r / min; the temperature range of the secondary screw extruder is controlled between 130 and 230° C., and the rotation speed is 10-20 r / min, and the foaming sheet is extruded through a sheet die; wherein a foaming agent is added at the end of the primary screw extruder, the foaming agent content is 6-12wt%, and the foaming agent pressure is 6-10MPa.

[0028] The foaming agent is one or more of supercritical carbon dioxide and supercritical nitrogen.

[0029] Compared with the prior art, the present invention has the following technical advantages:

[0030] 1) The present invention cleverly designs the order of adding materials, so that the excess epoxy chain extender reacts with the PLA resin first. The epoxy group on the PLA reacts with the ionic liquid added later to form a cross-linked structure, which is beneficial to locking the foaming agent. At the same time, the ionic liquid absorbs and captures the CO2 acid gas, adsorbs the foaming agent, improves the foaming ratio, and prepares a foamed sheet with high foaming ratio and high strength.

[0031] 2) The prepared PLA alloy is foamed using an environmentally friendly supercritical CO2 foaming agent, and the obtained foamed sheet has a foaming ratio of 23-27 times, a compression strength of 0.11-0.14Mpa, and a compression modulus of 3.5-3.8Mpa DETAILED DESCRIPTION

[0032] The present invention is further described below by means of specific examples. The examples described in the present invention are only used to illustrate the present invention and do not limit the scope of the present invention.

[0033] In each embodiment and comparative example, the sources of the main raw materials are as shown in Table 1 below:

[0034] Table 1 Raw materials and sources

[0035]

[0036]

[0037] The performance test parameters and corresponding test methods of PLA alloy and PLA foam are as follows in Table 2:

[0038] Table 2 Performance test methods

[0039] Test content unit Test Method Melt index g / 10min ISO 1133 Foaming ratio GB / T 6343 Cell diameter μm GB / T 12811 Cell density <![CDATA[per cm 3 > GB / T 12811 Compression strength MPa ASTM D1621 Compression modulus MPa ASTM D1621 Opening rate % GB / T 12811

[0040] The processing equipment used is:

[0041] Twin-screw extruder, Coperion, model ZSK 26 Mc 18, aspect ratio 52, screw diameter 26 cm;

[0042] Foam sheet tandem extruder, Shandong Tongjia Machinery Co., Ltd., the first-stage screw extruder has a length-to-diameter ratio of 40:1 and a screw diameter of 35cm, and the second-stage screw extruder has a length-to-diameter ratio of 25:1 and a screw diameter of 65cm.

[0043] The test equipment used is:

[0044] German Gottfert melt index instrument, test conditions are 190℃, 21.6kg (the melt strength of the material prepared this time is very high, and it cannot be measured under the conditions of 190℃, 2.16kg, so the test conditions are set to 190℃, 21.6kg);

[0045] German ZWICK impact testing machine, tensile test condition is 23℃;

[0046] Test Instruments Foam Density Tester;

[0047] Zeiss EVO series scanning electron microscope.

[0048] Example 1

[0049] Using the formula components in Table 3 as raw materials and referring to the raw material amounts in Table 3, PLA alloys were prepared according to the following method:

[0050] a. First, dry the PLA resin in a dehumidifying drying oven at 90°C for 6 hours;

[0051] b. PLA resin LX575 (acid value: 14 mol / T), talcum powder, anti-hydrolysis agent, chain extender ADR4468, antioxidant and plasticizer were mixed in a high-speed mixer, wherein the amount of ADR4468 was 0.7 wt %, the mixing speed was set to 60 rpm, the mixing time was 10 minutes, the main feed of the twin-screw extruder was added, and the ionic liquid tetramethylethylenediamine sulfonic acid onium salt was added to the liquid feed port of the middle section of the extruder, followed by melt extrusion. The extrusion conditions were: screw speed 200 rpm, and the screw temperature was set to 160° C., 170° C., 170° C., 175° C., 180° C., 180° C., 180° C., 190° C., 200° C., 200° C., 200° C. from the feed port to the die head in sections;

[0052] c. Cooling the extruded material in the water tank of the extruder, pelletizing, and drying in a vacuum oven at 90° C. for 4 h to obtain the PLA alloy;

[0053] d. Add PLA alloy to the extrusion foaming machine. After the melt is plasticized and mixed in the first-stage extrusion, inject the foaming agent supercritical CO2 5wt% into the first-stage screw extruder. The injection pressure of the foaming agent is 3.5Mpa. Set the temperature of the first zone of the first-stage screw to 170℃, the temperature of the second zone to 190℃, the temperature of the third zone to 210℃, and the temperature of the fourth zone to 240℃. The extrusion speed of the first-stage screw extruder is 50r / min, and the melt pressure is controlled at 10MPa.

[0054] The temperature of the first zone of the secondary screw was set to 220°C, the temperature of the second zone was set to 200°C, the temperature of the third zone was set to 180°C, and the temperature of the fourth zone was set to 160°C. The extrusion speed of the secondary screw extruder was 20r / min, and the melt pressure was controlled at 10MPa. The extruded foamed sheet was cooled, split, flattened, pulled, and rolled to finally obtain the PLA foamed sheet, and the pulling speed was 10m / min.

[0055] Example 2

[0056] PLA alloy was prepared according to the following method using the formula components in Table 3 as raw materials and referring to the raw material dosage in Table 3. Except for the following conditions, the other conditions refer to Example 1: The extrusion conditions of the twin-screw extruder are: screw speed 300rpm, screw temperature from the feed port to the die section is set to: 170℃, 170℃, 175℃, 175℃, 175℃, 175℃, 180℃, 180℃, 190℃, 190℃, 190℃; PLA alloy was added to the extrusion foaming machine, and the temperature of the first zone of the primary screw was set to 180℃, the temperature of the second zone was 210℃, the temperature of the third zone was 220℃, and the temperature of the fourth zone was 250℃. The extrusion speed of the primary screw extruder was 50r / min, and the melt pressure was controlled at 11MPa.

[0057] The temperature of the first zone of the secondary screw was set to 230°C, the temperature of the second zone was set to 200°C, the temperature of the third zone was set to 170°C, and the temperature of the fourth zone was set to 140°C. The extrusion speed of the secondary screw extruder was 10r / min, and the melt pressure was controlled at 11MPa.

[0058] Example 3

[0059] PLA alloy was prepared according to the following method with the raw material dosage in Table 3. Except for the following conditions, the other conditions refer to Example 1: The extrusion conditions of the twin-screw extruder are: screw speed 400rpm, screw temperature from the feed port to the die is set to: 170℃, 170℃, 170℃, 170℃, 170℃, 180℃, 190℃, 200℃, 200℃, 210℃, 210℃; PLA alloy was added to the extrusion foaming test machine, and the temperature of the first zone of the primary screw was set to 190℃, the temperature of the second zone was 200℃, the temperature of the third zone was 235℃, and the temperature of the fourth zone was 260℃. The extrusion speed of the primary screw extruder was 30r / min, and the melt pressure was controlled at 9MPa.

[0060] The temperature of the first zone of the secondary screw was set to 240°C, the temperature of the second zone was set to 180°C, the temperature of the third zone was set to 150°C, and the temperature of the fourth zone was set to 130°C. The extrusion speed of the secondary screw extruder was 10r / min, and the melt pressure was controlled at 9MPa.

[0061] Comparative Example 1

[0062] The PLA extruded foamed sheet was prepared using the raw materials in Example 1 and according to the method in Example 1, except that the order of adding the ingredients in the formula in Table 3 was different, and the ionic liquid and the chain extender were added simultaneously in the main feed.

[0063] Comparative Example 2

[0064] The PLA extruded foam sheet was prepared using the raw materials in Example 1 and according to the method in Example 1, except that the formula composition in Table 3 was different and the content of the epoxy chain extender was lower, with the addition amount being 0.2 wt %.

[0065] Comparative Example 3

[0066] The PLA extruded foamed sheet was prepared using the raw materials in Example 1 and according to the method in Example 1, except that the formula composition in Table 3 was different and no ionic liquid was added.

[0067] The performance test results of the foamed sheets obtained in Examples 1-3 and Comparative Examples 1-3 are shown in Table 4.

[0068] Table 3 Raw materials and amounts (wt%) in Examples 1-3 (S1-S3) and Comparative Examples 1-3 (D1-D3)

[0069]

[0070]

[0071] Table 4 Performance test results of products of Examples 1-3 (S1-S3) and Comparative Examples 1-3 (D1-D3)

[0072] Test items S1 S2 S3 D1 D2 D3 Melt index (g / 10min) 52 44 47 55 101 86 Foaming ratio (times) 25 27 23 11 9 8 <![CDATA[Foam density (g / cm 3 )]]> 0.050 0.046 0.054 0.113 0.138 0.155 Cell diameter (μm) 109-226 125-217 190-305 335-723 310-567 934-1530 Compression strength(MPa) 0.116 0.139 0.122 0.056 0.072- 0.047 Compression modulus (MPa) 3.65 3.77 3.59 1.11 1.27 0.92

[0073] It can be seen from Comparative Example 1 and Examples 1-3 that if the auxiliary agent is added from the main feed at the same time, the ionic liquid will first react with the epoxy chain extender to crosslink, and cannot be grafted onto PLA, and has poor compatibility with PLA. The foam cells finally prepared are uneven. It can be seen from Comparative Example 2 and Examples 1-3 that when less epoxy chain extender is added, PLA undergoes a crosslinking reaction before the addition of the ionic liquid, so that there are no excess epoxy groups to react with the ionic liquid, and a crosslinking structure cannot be formed. The foamed product finally obtained has a low foaming ratio. It can be seen from Comparative Example 3 and Examples 1-3 that pure PLA foaming has poor compatibility with CO2 and lacks pore nucleation points. The pores collapse after foaming and the foaming ratio is low.

[0074] The invention cleverly designs the order of adding materials and calculates the amount of epoxy chain extender to be added according to the acid value of the added PLA resin, so that the epoxy chain extender reacts with the PLA resin first. The epoxy group on the PLA reacts with the ionic liquid added later to form a cross-linked structure, which is beneficial for locking the foaming agent. At the same time, the ionic liquid absorbs and captures the CO2 acid gas to adsorb the foaming agent, thereby improving the foaming ratio and preparing a foamed sheet with high foaming ratio and high strength.

[0075] The above is only a preferred embodiment of the present invention. It should be pointed out that ordinary technicians in this field can make several improvements and supplements without departing from the method of the present invention. These improvements and supplements should also be regarded as the scope of protection of the present invention.

Claims

1. A PLA alloy comprising the following components in parts by weight: The chain extender is one or more of BASF's ADR4468, ADR4370, and ADR4400; The ionic liquid is one or more of tetramethylethylenediamine sulfonate onium salt, trioctylmethylamine bistrifluoromethanesulfonyl imide salt, and 3-[(3-acrylamidopropyl)dimethylammonium]propionate; The preparation method of the PLA alloy comprises the following steps: mixing PLA resin, talcum powder, anti-hydrolysis agent, chain extender, antioxidant and plasticizer, adding the mixture to the main feeding port of a twin-screw extruder, adding an ionic liquid to the middle section of the extruder, then melting and extruding, cooling, pelletizing and drying.

2. The PLA alloy according to claim 1, comprising the following components in parts by mass:

3. The PLA alloy according to claim 1, characterized in that The melt index of the PLA resin is 2-8 g / 10 min, and the test conditions are 190° C. and 2.16 kg.

4. The PLA alloy according to claim 1, characterized in that The melt index of the PLA resin is 4-7 g / 10 min, and the test conditions are 190° C. and 2.16 kg.

5. The PLA alloy according to claim 1, characterized in that: The PLA resin is selected from one or more of LX575, LX175, LX530 of Total Corbion, 4032D, 8052D, 2002D of Natureworks, REVODE110, REVODE190, REVODE101 of Zhejiang Hisun, FY801, FY802, FY804 of Anhui Fengyuan, and LX575 and LX175 of Total Corbion.

6. The PLA alloy according to claim 1, characterized in that: The anti-hydrolysis agent is one or more of monomeric carbodiimide and polymeric carbodiimide.

7. The PLA alloy according to claim 1, characterized in that: The anti-hydrolysis agent is one or more of STABAXOL 1LF of Rhein Chemie, HyMax 210 and HyMax 1010 of Langyi Chemical.

8. The PLA alloy according to claim 1, characterized in that The antioxidant is one or more of an amine antioxidant, a hindered phenol antioxidant, a thioester antioxidant, and a phosphite antioxidant.

9. The PLA alloy according to claim 1, characterized in that: The plasticizer is one or more of tributyl citrate, epoxidized soybean oil, monoglyceride, and dibutyl adipate.

10. A method for preparing a foamed sheet, comprising the following steps: The PLA alloy according to any one of claims 1 to 9 is extruded into a foamed sheet on a foaming extruder, and the foaming agent is one or more of supercritical carbon dioxide and supercritical nitrogen.

11. A foamed sheet prepared by the method according to claim 10, characterized in that: The foaming ratio of the foamed sheet is 23-27 times, the compression strength is 0.11-0.14Mpa, and the compression modulus is 3.5-3.8Mpa.

Citation Information

Patent Citations

  • Hexahedral silsesquioxane-based hyperbranched polymer and application of polymer in supercritical carbon dioxide foaming

    CN103910820A

  • Preparation method of high-rate polylactic acid foaming sheet

    CN109762313A

  • Method and device for directly preparing polylactic acid foam product from polylactic acid polymer melt

    CN109776848A

  • A system for capturing and releasing acid gases

    CN112426865A

  • Polylactic acid-based foaming particles and preparation method thereof

    CN112940468A